The Authority of The Village Head To Increase The Welfare of Farmers In Pinomontiga Village, Bulawa District, Bone Bolango Regency - Tri Infantry Kadir (Estudiante Law Journal, 2019)
Abstract: The purpose of this study was to determine the authority of the village head towards improving the welfare of farmers in Pinomontiga Village, Bulawa District, Bone Bolango Regency. The research method used is a normative-empirical legal research dualism where the research uses a normative-empirical legal case study in the form of a product of legal behavior. The approach used is a juridical approach and analytical techniques using qualitative analysis methods. The results of the study show that until now the performance authority or role of the village head of Pinomontiga Village has not been effective in improving the welfare of farmers, is based on several indicators as described, ranging from the lack of policy interventions that are pro to the welfare of farmers to the problem of providing very small agricultural assistance and incentives for farmers, while if you read carefully about the very large number of village income and expenditure budgets in Pinomontiga Village, you should be able to portion the budget for improving the welfare of farmers, which in terms of numbers and jobs are very large. The village has the authority to improve the welfare of farmers, although it is not maximal as the data obtained, it is better to increase the cooperation with the Village Consultative Body which increasingly always accommodates the aspirations of the community, so that from here on The village head as a leader in the village can know who the community is who needs a helping hand in the form of assistance for the welfare of the community.Keywords: Authority; Village head; Well-being